Kebijakan Hutan Kemasyarakatan (HKM) Di Kabupaten Tanggamus Provinsi Lampung - Dian Kagungan (PUBLICA, 2012)
This study aims to determine the local wisdom in the management of community forests in regency of Tanggamus Lampung by remain pay attention to the principle of balance of ecological function and social function of economic subsistence of local communities in accordance spirit community forestry program through the facilitation of activities in the Community Forestry Group of Tanggamus. Study came to the conclusion that the proper strategy is needed to build self-reliance and cooperation at the level of community forest farmer groups in order to reduce the dependence of farmers on the presence of facilitators and put farmers in a position key actors through the development of sustainable forest development of media / participatory tools as an alternative to filing an accelerated process of community forestry permission in the future. The study recommends institutional strengthening efforts should be made to all stakeholders on the development of competent Community forestry ( HKM ) .